MODEL GERAK DASAR BERBASIS MULTIMEDIA INTERAKTIF TERHADAP KETERAMPILAN GERAK DASAR SISWA SEKOLAH DASAR - M. Fahri Arridho; Nurkadri Nurkadri; Mufti Abdillah; Chrystian Rambe; Josafat Franata L. Sormin; Fatimah Zahra Wardani (UPT Publikasi dan Pengelolaan Jurnal Universitas Islam Kalimantan Muhammad Arsyad Al Banjari Banjarmasin, 2023)
The purpose of this study is to determine how well elementary school students are influenced by interactive multimedia-based basic motion models. An experiment with a one-group pre-test-post-test design was used for the research. The example of this exploration is 1st grade primary school understudies. The outcomes during the pre-test with a typical worth of 184.55 while the consequences of the typical post-test score were 265.425 intending that there was an increment of 44%. The t-count value is 42.389 and the t-table value is 1.685 in the significance test of the difference, indicating that there is a significant difference between the two groups before and after receiving an interactive multimedia-based basic motion model. According to this data, elementary school students are significantly influenced by the basic motion model.